2020
DOI: 10.1002/da.23095
|View full text |Cite
|
Sign up to set email alerts
|

Association of anger attacks with suicidal ideation in adults with major depressive disorder: Findings from the EMBARC study

Abstract: Background: This report evaluates whether anger attacks (sudden uncharacteristic bouts of anger that are associated with autonomic arousal and/or aggression) in patients with major depressive disorder (MDD) are associated with elevated suicidal ideation (SI; active suicidal thoughts and plans). Methods: Participants of Establishing Moderators and Biosignatures of Antidepressant Response in Clinical Care (EMBARC) study who completed Massachusetts General Hospital Anger Attack Questionnaire (AAQ) at baseline wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In both cases, anger is considered a transdiagnostic feature in several mental disorders, 5 including suicidal behavior, 6,7 and suicidal ideation. 8 Shri et al 9 found a relationship between irritable mood and suicidal behavior in a thorough analysis of suicide attempts.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, anger is considered a transdiagnostic feature in several mental disorders, 5 including suicidal behavior, 6,7 and suicidal ideation. 8 Shri et al 9 found a relationship between irritable mood and suicidal behavior in a thorough analysis of suicide attempts.…”
Section: Introductionmentioning
confidence: 99%